2013
DOI: 10.1128/aem.02541-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Logging and Forest Conversion to Oil Palm Plantations on Soil Bacterial Communities in Borneo

Abstract: cTropical forests are being rapidly altered by logging and cleared for agriculture. Understanding the effects of these land use changes on soil bacteria, which constitute a large proportion of total biodiversity and perform important ecosystem functions, is a major conservation frontier. Here we studied the effects of logging history and forest conversion to oil palm plantations in Sabah, Borneo, on the soil bacterial community. We used paired-end Illumina sequencing of the 16S rRNA gene, V3 region, to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
103
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 64 publications
(66 reference statements)
24
103
2
Order By: Relevance
“…Our results also imply that fungi may be more sensitive to logging than soil bacterial communities, as a recent study found that bacterial communities were compositionally distinct in oil palm soils, but were not different between primary and logged forests [44]. The differences in soil physical and chemical properties across land-use types likely explains some of the differences we observed [51], although further analysis and experimentation will be necessary, as differences in fungal composition across sites are likely due to a combination of other biotic and abiotic factors that have not yet been measured.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our results also imply that fungi may be more sensitive to logging than soil bacterial communities, as a recent study found that bacterial communities were compositionally distinct in oil palm soils, but were not different between primary and logged forests [44]. The differences in soil physical and chemical properties across land-use types likely explains some of the differences we observed [51], although further analysis and experimentation will be necessary, as differences in fungal composition across sites are likely due to a combination of other biotic and abiotic factors that have not yet been measured.…”
Section: Discussionsupporting
confidence: 67%
“…Palm oil, the commercial commodity extracted from oil palm fruits and kernels, is currently the most lucrative vegetable oil crop in the world, and Indonesia and Malaysia alone account for more than 80 % of all palm oil production [40,43]. To date, only a single culture-independent study has been conducted in oil palm agricultural soils in Malaysia, which found that bacterial communities were dramatically different in these ecosystems relative to primary and logged forests [44]. While there have been some small-scale studies examining the diversity of fungi in oil palm plantations [45,46], these have mostly focused on decomposer fungi and no molecular studies have evaluated soil fungal communities in these agricultural landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of noticeable tree removal due to selective logging and a modified tree composition resulting in abundant pioneer species (S. Both, unpublished data), our study revealed that the soil chemical and microbial properties were remarkably similar in both land‐use types. The soil microbial communities under tropical forests can be resilient to disturbance from logging (Lee‐Cruz, Edwards, Tripathi, & Adams, 2013; Tripathi et al., 2016), which may apply to our study system. However, despite similar free‐living microbial community composition, differences in the rate of loss of nutrients from litter suggest functional differentiation between communities.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that bacterial community diversity was most affected by agricultural practices (only 30% similarity compared with the microbial community present in the NF soil sample). Previously, it has been reported that there were greater shifts in the bacterial community in response to the conversion of tropical forest soils to oil palm plantations than logging activities [51] as well as long term fertilizer amendments [52]. The microbial diversity of the RP soil sample was significantly different (41% different from fungal community and 50% different from Archaeal community) and occurred in a different cluster in PCA analysis compared with NF (Figure 3).…”
Section: Influence Of Land-use Change On the Soil Microbial Communitymentioning
confidence: 98%